(untitled) - Saint, Sanjay (Philadephia, 2004)
University of California, San Francisco. Practical reference of essential information in the major medical specialties, for residents and students preparing for boards. Concise presentation with mnemonics and algorithms. Outline format. Softcover. 16 U.S. contributors. DNLM: Internal Medicine - outlines.
Keywords: Internal medicine,Mnemonics,Internal medicine,Diagnosis, differential